1970
DOI: 10.13057/biodiv/d040106
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation analysis of spermatophyte in Taman Hutan Raya (Tahura) Seulawah, Aceh Besar

Abstract: The objectives of this study were to inventory of plant species, determine rank taxonomy of species, and to give information quantitative value of taxa for vegetation analysis. About 5 hectare of the Tahura region is belong to Inhutani IV Company, was chosen as research population of this study. Two and half of hectare (2,5 ha) of this region used as a observed area. The data was collected by transec and quadratic method. The observed area it was took 10 transec with 250 m of long for observed stations. Each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Based on their habitus, the undergrowth is classified as herbs (15 species), shrubs (14 species), lianas (3 types), ferns (6 species), and palms (1 species). Similar research has been conducted in the other pine forest area (Destaranti et al 2017;Djufri 2003;Kunarso and Azwar 2013;Purnomo et al 2018;Yusra et al 2017). In the pine forest owned by PT.…”
Section: Composition Of Undergrowth Vegetationsupporting
confidence: 73%
See 2 more Smart Citations
“…Based on their habitus, the undergrowth is classified as herbs (15 species), shrubs (14 species), lianas (3 types), ferns (6 species), and palms (1 species). Similar research has been conducted in the other pine forest area (Destaranti et al 2017;Djufri 2003;Kunarso and Azwar 2013;Purnomo et al 2018;Yusra et al 2017). In the pine forest owned by PT.…”
Section: Composition Of Undergrowth Vegetationsupporting
confidence: 73%
“…Several studies have been reported that undergrowth vegetation has the potency to be used as food, medicine, forage, and botanical insecticides (Abdiyani 2008;Hadi et al 2016). Djufri (2003) suggested that the presence of undergrowth vegetation could be used as an environmental indicator. In addition, undergrowth vegetation has an essential role in the forest ecosystem and microclimate (Hilwan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity of species was shown at the various growth stages of seedlings, saplings, and poles with SI values > 50%, while in the case of adult trees SI value was reported 46.75% which showed higher dissimilarity. Djufri (2003) suggests that if the SI value is greate0072 than 75% the similarity criterion is very high, while when it is in the range of 50 -75%, 25 -50%, and < 25% it comes under the categories of high similarity, low similarity, and very low similarity respectively. Many tree species are that are present in the large channel are not found in the small channel and vice versa.…”
Section: Species Similarity Index (Si)mentioning
confidence: 99%
“…When there were unidentified species, the samples were made into herbarium specimens to be further identified in Herbarium Bogorense in Bogor. To compute the importance value (IV) of each species, formula according to Cox [10] was applied as follows: NP = Relative Frequency (RF) + Relative Density (RD) + Relative Dominance (RD). The value of Species Diversity Index (H') ranged from 0-7 of the Shannon-Wienner were interpreted using the following criteria: If H' ≤ 1, category was very low; if H' ≥ 1-2, the category low; if H' ≥ 2-3, the category was medium; if H' ≥ 3-4, the category was high; and if H' ≥ 4 the category was very high [11,12,13,14].…”
Section: Vegetation Samplingmentioning
confidence: 99%